The Ethical and Legal Aspects of Fee Splitting in Healthcare - Abdolhassan Kazemi (حقوق بشر, 2010)
Imposing unnecessary medical and healthcare costs upon patients is in direct contrast with patient rights and the spiritual and historical values of medical practice and it seriously undermines the honor regarding doctors and healthcare teams. All medical oaths and affidavits have repeatedly emphasized on the fact that medical teams and staff must take precedence over the patient’s rights and gains rather than their own. Such oaths clearly state that healthcare imposers must fulfill their duty regarding the patient’s physical and mental comfort. In the event of fee splitting, the medical staff not only neglect and undermine the medical affidavits but also seriously damage the hard gained doctor-patient trust and the historical honor of their profession. Within the law and justice system in practice in the Islamic Republic of Iran, fee splitting in considered unacceptable and illegal and fee splitters may be pursued by law. The same is true in different societies and most medical councils and accepted ethical codes and guidelines. It is clearly stated in the fifth paragraph of the medical affidavit vowed by all Iranian medical students and doctors that fee splitting is considered amoral and even illegal and that healthcare and medical practices are not to be used as a means of gathering wealth for oneself. All Islamic religious leaders have also questioned the lawfulness of money and wealth earned by fee splitting. The act of fee splitting is also recognized as unethical and unlawful in the guidelines and codes affected by universal medicine societies.